2021
DOI: 10.1111/jwas.12844
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the yellow catfish (Pelteobagrus fulvidraco) in China inferred from microsatellite analyses: implications for fisheries management and breeding

Abstract: Analysis of genetic diversity and population structure of the yellow catfish (Pelteobagrus fulvidraco), an important commercial aquaculture species that is widely distributed throughout China's fresh waters, could contribute to scientific management and sustainable utilization of this species. To characterize the population genetic structure of yellow catfish across China, 448 individuals from 10 locations across North, Central, and South China were analyzed using 15 microsatellite loci. Moderate to high genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Genetic diversity aids in species adaptation and their ability to cope with the environment, and plays a key role in the persistence of species during evolution [1]. This study observed a relatively medium level of microsatellite genetic diversity in M. longidorsalis, ranging from 0.625 to 0.683, compared to M. rapidus (H O = 0.757 [21]). Fish belonging to the genus Microphysogobio exhibit relatively high genetic diversity [21].…”
Section: Genetic Diversity and Population Bottleneckmentioning
confidence: 59%
See 1 more Smart Citation
“…Genetic diversity aids in species adaptation and their ability to cope with the environment, and plays a key role in the persistence of species during evolution [1]. This study observed a relatively medium level of microsatellite genetic diversity in M. longidorsalis, ranging from 0.625 to 0.683, compared to M. rapidus (H O = 0.757 [21]). Fish belonging to the genus Microphysogobio exhibit relatively high genetic diversity [21].…”
Section: Genetic Diversity and Population Bottleneckmentioning
confidence: 59%
“…Microsatellites have been mainly reported in studies on the genetic structure and diversity of the Gobioninae subfamily. Consequently, significant genetic diversity and structures were reported [20][21][22]. Microsatellites are commonly analyzed in population genetics studies because of their high intraspecific polymorphism and codominance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites markers have been the most often used approaches in literature to examine the genetic variability of C. carpio (24). Microsatellites have an unusual role in population studies because of their neutrality in selecting samples, as well as the e ciency with which conclusions based on microsatellites can be parallelized and validated in different populations (25). In order to enhance water quality and boost the quantity of native shes, common carp and scale carp abundance may need to be decreased and maintained below ecological thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of high-throughput sequencing technology, it is now easier and cheaper to screen microsatellite markers, which also promotes their wide application. Microsatellite markers have been successfully applied in various studies on aquatic biology [ 9 , 10 , 11 , 12 ] and testudines [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%